Malignant glomus tumor of the foot: a case report - Souza Júnior, Eli Ávila; César Mendes, Eugenio; Costa Monteiro Silva , Maria Clara; Junqueira de Mello, Guilherme (Journal of the Foot & Ankle, 2025)
Glomus tumors are rare lesions, representing approximately 2% of all soft tissue tumors, and are most found in the subungual region of the extremities. We present a rare case of a malignant glomus tumor located in the plantar region of the foot in a young adult, which was treated surgically through wide local excision. Level of Evidence V; Diagnostic Studies; Expert Opinion.